Independent contribution of bronchoalveolar lavage and serum galactomannan in the diagnosis of invasive pulmonary aspergillosis. Issue 3 (12th April 2014) - Fisher, C.E.; Stevens, A.M.; Leisenring, W.; Pergam, S.A.; Boeckh, M.; Hohl, T.M.
Abstract The optimal combination of galactomannan index (GMI) testing for the diagnosis of invasive pulmonary aspergillosis (IPA) remains unclear. For diagnostic approaches that are triggered by clinical signs and symptoms in high‐risk patients, institutional variation remains, with some centers routinely relying on only serum GMI or bronchoalveolar lavage (BAL) GMI testing. In addition, use of mold‐active agents before diagnosis of IPA is becoming increasingly common, and understanding the effect of these drugs on test yield is important when making time‐critical treatment decisions. In a single‐center cohort of 210 allogeneic hematopoietic cell transplant recipients, we found that serum and BAL GMI testing contributed independently to IPA diagnosis, supporting the practice of sending both tests simultaneously to ensure a timely diagnosis of IPA. BAL GMI sensitivity was not affected by receipt of mold‐active therapy in our cohort.